Use of a negative binomial distribution to describe the presence of Sphyrion laevigatum in Genypterus blacodes - Patricio Peña-Rehbein; Patricio De los Ríos-Escalante; Raúl Castro; Carolina Navarrete (Revista Brasileira de Parasitologia Veterinária)
This paper describes the frequency and number of Sphyrion laevigatum in the skin of Genypterus blacodes, an important economic resource in Chile. The analysis of a spatial distribution model indicated that the parasites tended to cluster. Variations in the number of parasites per host could be described by a negative binomial distribution. The maximum number of parasites observed per host was two.